Benefit–Cost Analysis of Foot-and-Mouth Disease Vaccination at the Farm-Level in South Vietnam - Truong, Dinh Bao; Goutard, Flavie Luce; Bertagnoli, Stéphane; Delabouglise, Alexis; Grosbois, Vladimir; Peyre, Marisa (Frontiers in Veterinary Science, 2018)
This study aimed to analyse the financial impact of foot-and-mouth disease (FMD) outbreaks in cattle at the farm-level and the benefit-cost ratio (BCR) of biannual vaccination strategy to prevent and eradicate FMD for cattle in South Vietnam. Production data was collected from 49 small-scale dairy farms, 15 large-scale dairy farms and 249 beef farms of Long An and Tay Ninh province using a questionaire. Financial data of FMD impacts was collected using participatory tools in 37 villages of Long An province. The net present value, i.e. the difference between the benefits (additional revenue and saved costs) and costs (additional costs and revenue foregone), of FMD vaccination in large-scale dairy farms was 2.8 times higher than in small-scale dairy farms and 20 times higher than in beef farms. The benefit-cost ratio of FMD vaccination over one year in large-scale dairy farms, small-scale dairy farms and beef farms were 11.6 (95% confidence interval (95% CI) 6.42-16.45), 9.93 (95% CI 3.45-16.47) and 3.02 (95% CI 0.76-7.19), respectively. The sensitivity analysis showed that varying the vaccination cost had more effect on the BCR of cattle vaccination than varying the market price. This benefit-cost analysis of biannual vaccination strategy showed that investment in FMD prevention can be financially profitable, and therefore sustainable, for dairy farmers. For beef cattle, it is less certain that vaccination is profitable. Additional benefit-cost analysis study of vaccination strategies at the national-level would be required to evaluate and adapt the national strategy to achieve eradication of this disease in Vietnam.